PENGARUH PEMBERIAN FASILITAS PENUNDAAN DAN TINGKAT PRODUKSI ROKOK TERHADAP PENERIMAAN CUKAI (STUDI PADA PERUSAHAAN ROKOK YANG TERDAFTAR DI KPPBC TMC KUDUS) - Dyah - Novitasari; Suryadi - Poerbo; Sri Eka Sadriatwati (Politeknik Negeri Semarang, 2018)
The aim of this research is to analyze the influence of excise postponement facility and production level on excise revenue in KPPBC TMC Kudus. This research is an explanatory research with quantitative approach. Secondary data used are monthly period data from January 2015- December 2017, obtained from Department of excise, Directorate General Customs and Excise. The analysis uses the multiple of linier regression statistic. The result shows that 25% the variance of independent variables can explain the variation of excise revenue. The excise postponement facility and production level simultaneously have significant influence on excise revenue with significant level at α = 5%. Partially, it showed that postponement facility had positif significantly to excise revenue. Subsequently, the production level influence positif significantly to the excise revenue. The result implication is the importance role to increase amount of postponement facility and intensify supervision and service to support the cigarette companies increase production of a good quality product.